2020
DOI: 10.1002/jcp.29956
|View full text |Cite
|
Sign up to set email alerts
|

α5‐nAChR and survivin: Two potential biological targets in lung adenocarcinoma

Abstract: Recent studies have shown that the overexpression of α5 nicotinic acetylcholine receptor (α5-nAChR) is associated with nicotine-related lung carcinogenesis. Survivin is one of the biomarkers of a worse prognosis for smoking-related lung cancer. The aim of this study is to investigate the association of α5-nAChR, survivin, and clinical outcomes in lung adenocarcinoma (LUAD). We analyzed the expression level and correlation of CHRNA5 (encoding α5-nAChR) and BIRC5 (encoding survivin) in LUAD with The Cancer Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Aberrant expression of some genes may mediate nicotine-induced carcinogenesis. For example, nicotine exposure can elevate the expression of α5 nicotinic acetylcholine receptors and survivin in lung cells, which plays an important role in the occurrence and development of lung adenocarcinoma [ 9 ]. Nicotine exposure can also induce the abnormal expression of PRX1 and the genes encoding for its interacting proteins CFL1 and PPP2R1A , thereby promoting the transformation of normal oral cells into cancer cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression of some genes may mediate nicotine-induced carcinogenesis. For example, nicotine exposure can elevate the expression of α5 nicotinic acetylcholine receptors and survivin in lung cells, which plays an important role in the occurrence and development of lung adenocarcinoma [ 9 ]. Nicotine exposure can also induce the abnormal expression of PRX1 and the genes encoding for its interacting proteins CFL1 and PPP2R1A , thereby promoting the transformation of normal oral cells into cancer cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the present study, BIRC5 emerged as the most significant IAP that could be developed as a marker for preventing and treating NSCLC patients. Low expression of BIRC5 mRNA was also previously positively correlated with NSCLC patient survival ( Cao et al, 2019 ; Nitschkowski et al, 2019 ; Rashed et al, 2019 ; Zhang et al, 2020b ).…”
Section: Discussionmentioning
confidence: 74%
“…Consistently, we found that BIRC5 expression levels were significantly higher in tumor tissues than in normal tissues. Previous studies have suggested BIRC5 as a predictive biomarker in NSCLC, especially for LUAD ( Zhang et al, 2020b ; Haakensen et al, 2020 ). In addition, in the present study, BIRC5 emerged as the most significant IAP that could be developed as a marker for preventing and treating NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…BIRC5 is a member of the inhibitors of apoptosis (IAP) gene family, which encodes negative regulatory proteins that prevent apoptotic cell death. Unlike other IAPs, BIRC5 expresses intensely in most tumors, including LUAD and LUSC [ 55 ], and it could serve as a predictive biomarker for NSCLC, especially for LUAD [ 56 ], but does not express or only expresses at low levels in most normally differentiated tissues [ 57 ], and down-regulated BIRC5 was positively associated with NSCLC survival time [ 58 ]. Cell division cycle 6 ( CDC6 ) is an important regulator of DNA replication, and there is evidence that silencing of CDC6 may lead to G1 phase arrest [ 59 ].…”
Section: Resultsmentioning
confidence: 99%